Mortonagrion indraneil spec. nov. from Borneo, and a redescription of M. arthuri Fraser (Odonata: Zygoptera: Coenagrionidae) - Dow, Rory A. (Zootaxa, 2011)
M. indraneil spec. nov. is described from locations in Sarawak, Malaysian Borneo. Both sexes of M. arthuri Fraser are re-described based on recent material. Records of M. amoena Ris from Borneo in fact refer to M. indraneil; there is no evidence that M. amoena occurs on Borneo. Relationships between Argiocnemis, Agriocnemis and Mortonagrion are discussed.